Mechanisms of Lushi Runzao decoction in Treating Sjögren’s syndrome by remodeling gut flora to regulate bile acid and short-chain fatty acid metabolism - Pang, Fengtao; Jiang, Quan; Tang, Xiaopo; Li, Kesong (Frontiers in Pharmacology, 2025)
ObjectiveTo explore the mechanisms of Lushi Runzao decoction (LSRZT) in Treating Sjögren’s Syndrome (SS) through gut flora, short-chain fatty acid (SCFAs) and metabolomics.MethodsNon Obese Diabetes (NOD) /LtJ mice were used as the model group, LSRZT and hydroxychloroquine (HCQ) were administered to the treatment group. Fecal samples were collected 4 weeks after the intervention. The microbiota, SCFAs and metabolites were analyzed using 16S ribosomal Ribonucleic Acid, Gas chromatography mass spectrometry analysis and Ultra High Performance Liquid Chromatography-Quadrupole Time-of-Flight Mass Spectrometry.ResultsLSRZT had obvious anti-inflammatory effect and can effectively improve the functional injury of submandibular gland; It improves the imbalance of gut microbiota and the related metabolic levels of SCFAs and bile acids, and regulates the levels of inflammatory factors and the contents of bile acids and caproic acid by regulating the abundance of Erysipelatoclostridiaceae, Gammaproteobacteria and Ruminococcaceae.ConclusionLSRZT can reduce the level of inflammation and improve the imbalance of gut microbiota and metabolism. It provides a scientific basis for the clinical treatment of SS by LSRZT.